Supervised resistance training session increases the volume load and the subjective responses in well-trained men - Charles Ricardo Lopes; Enrico Gori Soares; Luan Oenning; Felipe Alves Brigatto; Paulo Henrique Marchetti (Journal of Physical Education (Maringá), 2020)
Supervised resistance training may affect several acute variables such as volume load (VL), the maximum number of repetitions  (NRM),  time under tension (TUT), and rate of perceived exertion (RPE) in resistance trained-men. The present study aimed to evaluate the influence of the personal trainer’s supervision on a resistance training session in resistance trained-men. Fifteen resistance-trained men (20,0±2 years; 176,0±4 cm; 79,3±4,7 kg)  performed two training sessions composed of whole-body exercises. In the session without personal trainer’s supervision (NPT) the subjects self-selected their loads for each exercise and were oriented to “select a load typically employed to perform 10 repetitions”; in the session with personal trainer’s supervision (WPT) the subjects self-selected their loads for each exercise and were oriented to “perform maximum effort”. It was observed greater VL (P<0,001, Δ%=30), NRM (P<0,001, Δ%=29), TUT (P=0,003, Δ%=21), and RPE (P<0,001, Δ%=29) in the resistance training session WPT. The present study concluded that supervised sessions positively affect resistance training variables.